2013
DOI: 10.1021/ja311090e
|View full text |Cite
|
Sign up to set email alerts
|

Selective Tumor Cell Targeting by the Disaccharide Moiety of Bleomycin

Abstract: In a recent study, the well documented tumor targeting properties of the antitumor agent bleomycin (BLM) were studied in cell culture using microbubbles that had been derivatized with multiple copies of BLM. It was shown that BLM selectively targeted MCF-7 human breast carcinoma cells, but not the “normal” breast cell line MCF-10A. Further, the BLM analogue deglycobleomycin, which lacks the disaccharide moiety of BLM, was found not to target either cell line, indicating that the BLM disaccharide moiety is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
201
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(207 citation statements)
references
References 22 publications
4
201
0
2
Order By: Relevance
“…Recently, researchers have found that some specific molecules used as targeting agents, such as carbohydrate, 10 folic acid, 11,12 transferrin, 13,14 and some peptides, 15,16 could be modified onto the surface of NPs and achieve active targeting therapy with high specificity, selectivity, and affinity through coupling targeting molecules with their specific receptor expressed on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have found that some specific molecules used as targeting agents, such as carbohydrate, 10 folic acid, 11,12 transferrin, 13,14 and some peptides, 15,16 could be modified onto the surface of NPs and achieve active targeting therapy with high specificity, selectivity, and affinity through coupling targeting molecules with their specific receptor expressed on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Other common issues with nanocarriers are uncontrolled cargo release or rapid pharmacokinetic (PK) clearance. Great efforts have been made to remedy these problems; however, no carrier has effectively managed all these issues [1][2][3][4][5]. While many different formulations have been applied to PTX, there has been very little success thus earning it the description 'brickdust' [6].…”
Section: Abstract: Imaging • Long Circulation • Molecular-matched Nanmentioning
confidence: 99%
“…The lipid dispersion was then sonicated for 2 min (probe sonicator, output power 10 W, Fisher Scientific). 3 H-labeled nanoformulations were prepared by mixing a trace amount of 3 H-PTX, 3 H-PTX-VE or 3 H-PTX-LA in the mixtures as preliminary treatment.…”
Section: Preparation Of Molecular-matched Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleomycin (BLM) is a glycopeptid drug originally isolated from Streptomyces verticillus [19,20] is clinically used for cancer therapy [20,21]. The bleomycins are a family of glycopeptide-derived antitumor antibiotics used clinically for the treatment of squamous cell carcinomas and malignant lymphomas [22][23][24]. Their antitumor activity is due to selective oxidative cleavage of 5′-GC-3′ and 5′-GT-3′ sequences in DNA, and possibly also to RNA oxidative degradation [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%